Mechanism and treatment progress of disseminated intravascular coagulation in sepsis - ZHANG Jun, FENG Jianhong, DU Xianrong (Zhongguo linchuang yanjiu)
Sepsis is the main cause of death in critically ill patients in clinic, with high incidence and complicated pathogenesis. Coagulation system is an important factor of the pathogenesis and lethal mechanism of sepsis, especially sepsis complicated with disseminated intravascular coagulation (DIC), which is the dual effect of coagulation cascade reaction and inflammatory immune response. This paper describes the molecular mechanism and the latest treatment research progress of DIC in sepsis, in order to provide new ideas and methods for clinical work.